Fat Embolism Syndrome in Two Cases with Multiple Fractures - Ülkü Özgül; Ender Gedik; Mustafa Karakaplan; Elif Koç; Erdinç Koca; Türkan Toğal; Mehmet Özcan Ersoy (Galenos Yayinevi, 2012)
Fat embolism is a syndrome which is caused by oil particles introduce into the systemic circulation and consists of respiratory distress, altered consciousness and petechial rashes. It may occur following traumatic, surgical and non-traumatic clinical conditions. The most common occurrence develops following the long bone fractures within 24-72 hours. The clinical picture of syndrome may vary slightly condition as well as respiratory failure and coma. The diagnosis is done based on mostly clinical criteria. There is no specific laboratory and radiographic findings. The suggested supportive approaches in the treatment of this syndrome are early fixation of the fracture, maintenance of fluid and electrolyte balance and treatment of hypoxia. We aimed to present two cases of successful diagnosis and treatment process with fat embolism syndrome following multiple fractures due to in-vehicle traffic accidents. (Journal of the Turkish Society Intensive Care 2012; 10: 23-7)